Analisis Kelayakan Usaha Penyulingan Minyak Nilam Di Kecamatan Salang - Yusnaidi Yusnaidi; Julisarnewi Julisarnewi (universitas teuku umar, 2017)
ABSTRACT This research was conducted at Salang Subdistrict in the District of Simeulu. It was aimed to evaluate the visibility to run patchouli oil distilation business. The data is primary data collected from the distilation plant at Salang Subdistrict in the District of Simeulu.The data was analized through Net Present Valie (NPV), Internal Rate Return (IRR), Net Benefit Cost Ratio (net B/C), Payback Priod (PP) in order to evaluate the investment visibility.The result shows this business is visible to be done and invested. This conclusion is based on the result of the Net Present Valie (NPV), Internal Rate Return (IRR), Net Benefit Cost Ratio (net B/C), Payback Priod (PP) that shows positive result. Therefore the government should pay more attention to develop this business to grow and give more impact on community income. Key words: patchouli oil, distilation business, investment, visibility study.